Synthesis and Biological Activity of Some Substituted Phenyl Ureas - Dhingra, Vinod; Shrivastava, A.K. (Asian Journal of Chemistry, 2010)
Synthesis and anti-AIDS, anti-cancer, fungicidal, anti-bacterial activitiesof some new substituted α(2' -chloro-5'-nitro) benzamido-4-N,N-bis-2'-cyano-ethylaminocinnamo substituted phenylureas are reported.